A Case of Lipomatous Pseudohypertrophy of the Pancreas Diagnosed by Typical Imaging - Yasuda, Mikihiko; Niina, Yusuke; Uchida, Masahiko; Fujimori, Nao; Nakamura, Taichi; Oono, Takamasa; Igarashi, Hisato; Ishigami, Kousei; Yasukouchi, Yumi; Nakamura, Kazuhiko; et al. (JOP. Journal of the Pancreas, 2010)
Context Lipomatous pseudohypertrophy of the pancreas is an extremely rare disease, and is characterized by the replacement of pancreatic acinar cells with adipose tissue, although the pancreatic duct and islets are preserved. Case report We report the case of a 64-year-old female who was undergoing treatment for Hashimoto’s disease at a nearby clinic. For the previous two years, she had experienced an unpleasant feeling in the upper abdominal area after eating oily foods. For the previous six months, she had also suffered from lower-back pain, and presented at our hospital. Abdominal computed tomography and magnetic resonance imaging revealed marked fat replacement over the entire pancreas. Endoscopic retrograde cholangiopancreatography revealed no anatomical abnormality or narrowing of the main pancreatic duct; the main pancreatic duct was normal up to the pancreatic tail and the branches of the pancreatic duct did not show any abnormalities. While the serum levels of the pancreatic enzymes were considerably low, according to the data of the pancreatic exocrine function test (N-benzoyl-tyrosyl-p-aminobenzoic acid test), endocrine function was maintained. On the basis of the abovementioned findings, we diagnosed lipomatous pseudohypertrophy of the pancreas. Conclusions Lipomatous pseudohypertrophy of the pancreas is a very rare disease characterized by the disappearance of pancreatic exocrine tissue due to adipose tissue replacement, although the pancreatic duct and islets remain intact. Even though it has been suggested that the diagnosis of lipomatous pseudohypertrophy of the pancreas should be based on histological findings, this case indicated the possibility that lipomatous pseudohypertrophy of the pancreas may be diagnosed solely by typical imaging findings and serological data. Image: ERCP: There is no anomalous arrangement of the pancreaticobiliary ducts or any anomaly of the pancreatic ducts.